Recent developments in electrode materials for dual-ion batteries: Potential alternatives to conventional batteries. (January 2022) - Wang, Heng-guo; Wang, Yunong; Wu, Qiong; Zhu, Guangshan
Graphical abstract: Abstract: Lithium-ion batteries (LIBs), known as "rocking-chair batteries", have shown a huge success in consumer electronics and energy vehicles. However, the soaring cost caused by the shortage of lithium and cobalt resources as well as the need for ever-higher performance and safety has promoted an urgent need to develop high-efficient battery systems. Dual-ion batteries (DIBs), based on different working mechanism that involves both cations and anions during the charging/discharging processes, are expected to be an alternative to conventional batteries due to their environmental friendliness, low cost, excellent safety, high work voltage, and high energy density. Despite these merits, DIBs also face various challenges from the limited capacity caused by intercalation-type graphite electrodes and shorter cycle life resulted from large anions intercalation and electrolyte decomposition at high voltage. To overcome those challenges, various effective strategies have been adopted and many inspiring results have been also reported. In this review, we briefly outlined the history, mechanism and configuration of DIBs and mainly summarized the recent developments of electrode materials for DIBs, covering inorganic electrode materials and organic electrode materials, along with their application in various metal-based DIBs. Especially, recent studies on organic electrode materials based on so-called DIB working mechanism are also highlighted. In addition, the existing problems and future perspectives are finally proposed. We hope this review will provide some inspiration for researchers to rationally design more efficient electrode materials for more advanced DIB systems.